Readings for writers - McCuen, Jo Ray (Harcourt Brace Jovanovich, 1980)
EADINGS FOR WRITERS has been the preeminent rhetorical reader for the freshman composition course. This bestseller continues its tradition of providing comprehensive coverage of the writing and research process, while also offering a wide variety of appealing readings. With more than 100 selections from a broad range of topics and genres, this text offers something to spark excitement in any developing writer.